Relationship Between Children Under Five Years Characteristics, Age While Measles Immunization, History of Exclusive Breastfeeding with Clinical Measles - Linda Andriani (Jurnal Berkala Epidemiologi, 2017)
Measles cases in Indonesia are the second-highest measles case in the world after India. Measles cases in Indonesia were reported to reach 8,185 cases in 2015. The highest number of clinical measles in East Java was 606 cases in 2016 and has an upward trend from 2013 to 2016. Sidoarjo District is one of the cities/districts with the highest measles cases in East Java. This study aims to analyze the relationship between the characteristics of children under five, age of measles immunization, and history of exclusive breastfeeding (ASI eksklusif) with the incidence of clinical measles. This type of research is analytic observational with a cross-sectional design. This research was conducted at the Public health center (PHC) of Wonoayu Sidoarjo District in November 2016 - May 2017. The sampling technique uses simple random sampling. The number of samples studied was 61 children under five who were registered at the Integrated Management of Newborn and Childhood Illness (IMNCI). Primary data collection uses interview method with questionnaire guidelines, while secondary data uses monthly report recapitulation of C1 Wonoayu Health Center in 2017 and case-based measles surveillance (CBMS) recording from the East Java Provincial Health Office in January - April 2017. Data analysis using the Chi-square test. The results showed that there was a relationship between age at measles immunization (p = 0.010) and the history of exclusive breastfeeding (p = 0.045) on clinical measles. There was no relationship between the sex of children under five (p = 0.909) on clinical measles. The attention of health workers to the discipline of toddlers related to timely measles immunization is very important as well as the understanding of toddler mothers about the role of exclusive breastfeeding for children's immunity.